The Role Of Mismatches Between The Requirements Of A Job And The Characteristics Of Its Employer In The Performance Of Insurance Companies - الحمدان دريد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The objective of the study is to study the phenomenon of Education-Job Mismatches and its role in the performance of public companies, To achieve the objective of the study, the researcher conducted an exploratory study, which included the distribution of a preliminary survey and a number of direct interviews with a number of management experts in Syria, in addition to the design of a questionnaire, and 265 questionnaire was distributed to all workers with degrees (secondary, institutes, universities) at the Syrian General Insurance Corporation. The main results were: 1 - The rate of Education-Job Mismatches for employees of the Syrian General Organization for Insurance is 48%. 2 - There is a strong and positive correlation between (Education-Job Mismatches for employees) and (the performance of the Syrian General Organization for Insurance Insurance). The study recommended the necessity of adopting a strategy for binding human resources and monitoring their application in companies, especially the public according to specific regulations, and working to improve the working environment in companies (providing transportation for employees, developing an effective incentives and reward system), and the need for cooperation and coordination between the Ministry of Higher Education and Chambers of Commerce and Industry, The gap between education outputs and labor market requirements.